2020
DOI: 10.1186/s12891-020-03704-5
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil to lymphocyte ratio as a predictor for diagnosis of early Periprosthetic joint infection

Abstract: Background Periprosthetic joint infection (PJI) is a catastrophic complication after total knee or hip arthroplasty. The diagnosis of PJI is very difficult, especially in the early postoperative period. The value of the neutrophil to lymphocyte ratio (NLR) is useful for diagnosing infectious diseases. The objective of this study was to investigate the accuracy of the NLR for the diagnosis of early PJI after total knee or hip arthroplasty. Methods We retrospectively evaluated consecutive primary total knee or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 23 publications
2
49
2
Order By: Relevance
“…However, Zhao et al [23] and Yu et al [14] demonstrated that NLR and PLR had greater predictive value for diagnosis of PJI than ESR and CRP, in stark contrast to our results. Our further analysis indicated that this was most likely due to differences in the characteristics of the enrolled patients; in our study, examined patients were diagnosed as chronic PJI, but the other two studies [14,23] examined patients who had acute PJI .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, Zhao et al [23] and Yu et al [14] demonstrated that NLR and PLR had greater predictive value for diagnosis of PJI than ESR and CRP, in stark contrast to our results. Our further analysis indicated that this was most likely due to differences in the characteristics of the enrolled patients; in our study, examined patients were diagnosed as chronic PJI, but the other two studies [14,23] examined patients who had acute PJI .…”
Section: Discussioncontrasting
confidence: 99%
“…They used an NLR cutoff of 2.77, similar to our cutoff (2.71). Similarly, Yu et al [14] found that the NLR was effective in diagnosing PJI (AUC: 0.802, 85% sensitivity, 68.3% speci city, 34.7% PPV, 95.8% NPV) with a cut-off value of 2.13. However, Zhao et al [23] and Yu et al [14] demonstrated that NLR and PLR had greater predictive value for diagnosis of PJI than ESR and CRP, in stark contrast to our results.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Lower cut-off values were described by Glehr et al [13] (cut-off: 5.48 G/L) and Klim et al [20] (cut-off 5.68), leading to a higher sensitivity (91% and 90%, respectively) but at the expense of specificity (34% and 39%, respectively). Table 3 shows the recent literature of WBC depending on the used infection definition [2,10,11,13,[15][16][17]20,23,25,29,35].…”
Section: White Blood Cell Count (Wbc)mentioning
confidence: 99%
“…However, the available data reveals controversial results regarding the performance of IL-6. A proper comparison cannot be made due to the different infection definitions and cut-offs (Table 6) [11,13,15,16,18,23,25,80]; hence, no recommendation can be given. Further studies are needed to elucidate the diagnostic value of IL-6 in diagnosing PJI.…”
Section: Interleukin-6 (Il-6)mentioning
confidence: 99%